"Green Medicine": The Past, Present, and Future of Botanicals. Issue 3 (27th August 2018) - Paine, Mary F.; Roe, Amy L.
Abstract : Botanicals are plant‐derived products that have been consumed by humans for centuries. Today, the marketing and use of botanicals for health and wellness benefits continues to thrive worldwide, with consumers projected to spend more than $140 billion globally by 2024 (Global Analysis, Inc).1 However, research on the quality and safety of these products has lagged behind sales. Because of this divergence, opportunities abound for collaborations amongst scientists from industry, academia, and government to address these unmet public health needs. Clinical pharmacologists and toxicologists from all of these sectors play critical roles in developing harmonized approaches to achieve the common goal of ensuring botanical products with superior quality and safety.